Culture Negative Endocarditis With Tropheryma whipplei - Jennifer M. Bergeron; Trace C. Barrett; Allen B. Repp (Annals of Internal Medicine: Clinical Cases)
Tropheryma whipplei endocarditis is an increasingly recognized cause of culture negative endocarditis but is challenging to diagnose and often not accompanied by typical symptoms of Whipple disease. In this report, we describe a case of T. whipplei endocarditis and share echocardiographic images from the patient case.